Selection proposal of cultivars of spring barley in the years from 2001 to 2004, using the joint regression analysis - Pereira, Dulce G. (2012)
Joint Regression Analysis is a widely used technique in the analysis of series of experiments for cultivar comparison. We show how this technique may be used in the selection of recommended cultivars. We apply this technique to a series of experiments on spring barley cultivars carried out from 2001 to 2004. The data in these designs were kindly made available by the Central Institute for Supervising and Testing in Agriculture in Brno, Czech Republic.